Hypernatremia Masking a Case of Primary Sjögren Syndrome-induced Distal Renal Tubular Acidosis - Chinmaye Sapre; Abhishek Prajapati; Rohan Parikh (Saudi Journal of Kidney Diseases and Transplantation, 2023)
Distal renal tubular acidosis (dRTA), also known as Type 1 renal tubular acidosis, is a rare disorder. It primarily occurs through the inability to secrete H+ ions. The causes of dRTA can be divided into primary and secondary. The most common secondary cause of dRTA is Sjögren syndrome. dRTA typically presents as hypokalemia with non-anion gap metabolic acidosis. Here, we present a patient where Sjögren's syndrome causing dRTA was masked by the presence of hypernatremia causing metabolic acidosis with a high anion gap.